Pengembangan Podcast Menggunakan Aplikasi Youtube sebagai Media Pembelajaran untuk Melatih Kemampuan Siswa SMA Menganalisis Peristiwa Secara Kronologis - Gusvi, Elva Dwi; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
This research is motivated by the limited use of varied learning media by teachers, who mainly rely on textbooks and PowerPoint presentations dominated by text. Additionally, students often show low ability in analyzing historical events chronologically. This study aims to: (1) Determine the development process of Podcast-based learning media on the YouTube platform for history learning. (2) Assess the feasibility level of Podcast-based learning media on the YouTube platform in training students to analyze events chronologically. (3) Evaluate the practicality and effectiveness of Podcast-based learning media on the YouTube platform in training students to analyze events chronologically. The research method used is Research and Development (R&D) with the ADDIE model. The implementation of Podcasts as a learning medium was carried out in class XI/F3 of SMA N 13 Padang. The results of the study show that: (1) Podcasts as a learning medium were developed using the YouTube platform. (2) The feasibility of the Podcast as a learning medium is categorized as highly feasible, with an average validation score from subject matter experts of 3.83 and from media experts of 3.60. (3) The practicality results of the Podcast as a learning medium are also in the highly feasible category, with an average score of 3.88 from teachers and 3.52 from students. The effectiveness test, conducted using Google Forms with three questions, indicated that Podcasts are effectively used in the history learning process.